Islamic Play Counseling Approach to Fostering Honesty in Early Childhood - Syakila; Zuafni; Dhiya Susanti; Adi Fitra (al-Afkar, Journal For Islamic Studies, 2026)
Fostering honesty in early childhood is a fundamental aspect of education that supports moral and spiritual development from an early age. However, the value of honesty is often overlooked in instructional practices that focus solely on cognitive aspects. This study aims to analyze the implementation of an Islamic play counseling approach in cultivating honesty among young children in Islamic early childhood education (ECE) institutions. A qualitative research approach with a case study design was employed. Data were collected through participant observation, in-depth interviews with five ECE teachers, and documentation of learning activities, involving fifteen children aged 4–6 years as participants. Data analysis was conducted thematically using NVivo software to identify patterns in the development of honesty during Islamic play activities. The results indicate that Islamic play counseling utilizing educational games, storytelling about the Prophets, and role-playing consistently instills the value of honesty in children's daily behavior. These activities build children's understanding of the meaning of honesty through an enjoyable and contextual approach. In conclusion, the Islamic play counseling approach offers practical and theoretical contributions to character education and can be adopted by ECE teachers as a relevant instructional strategy for shaping positive character from an early age.